Unravelling Affective Mathematical Disposition: Its Role in Strengthening Numeracy Among Pre-Service Mathematics Teachers - Soesanto, Robert Harry; Dirgantoro, Kurnia Putri Sepdikasari (FKIP Universitas Lampung, 2025)
This study investigates the relationship between affective mathematical disposition (MD) and numeracy among pre-service mathematics teachers in Indonesia. The research examines explicitly how different dimensions of MD influence students' numeracy skills. A total of 237 participants took part in a semester-long numeracy enrichment program, followed by a numeracy assessment and an MD questionnaire based on Beyers' seven affective dimensions. Using multiple linear regression analysis, the findings indicate that MD significantly affects numeracy (p = 0.018), with an adjusted R-squared value of 0.571, indicating that 57.1% of the variance in numeracy scores can be explained by MD. Notably, the dimensions